Primary Systemic Amyloidosis and High Levels of Angiotensin-Converting Enzyme: Two Case Reports. (10th March 2013) - Praena-Segovia, J.; Sanchez-Gastaldo, A.; Bernabeu-Wittel, M.; Ocete-Pérez, R.; Ávila-Polo, R.; Martino, M. L.
Abstract : Infiltrative heart diseases are caused by a heterogeneous group of disorders; amyloidosis and sarcoidosis are two frequent causes of myocardial infiltration, which differ in clinical and biological outcome and treatment issues. The presence of high levels of angiotensin-converting enzyme (ACE) in a patient with infiltrative heart disease may increase suspicion of sarcoidosis. Nevertheless, no mention about increased ACE levels in extracerebral primary systemic amyloidosis is available. We present two cases of primary systemic amyloidosis, which are cardiac involvement and elevated ACE levels.